Moments That Matter? On the Complexity of Using Triggers Based on Skin Conductance to Sample Arousing Events Within an Experience Sampling Framework. Issue 5 (11th May 2020) - van Halem, Sjoerd; van Roekel, Eeske; Kroencke, Lara; Kuper, Niclas; Denissen, Jaap
Abstract: To sample situations that are psychologically arousing in daily life, we implemented an experience sampling strategy in which 82 Dutch young adults ( M age  = 20.73) were triggered based on random time intervals and based on physiological skin conductance scores across a period of 5 days. When triggered, participants had to fill in short surveys on affect, situational characteristics and event characteristics on their smartphone. We found theoretically expected relationships between the skin conductance signal on the one hand and self‐reported arousal and positive energy (e.g. energetic and enthusiastic) on the other hand, although effect sizes were small. Unexpectedly, none of the negative affective scales (i.e. irritation, anxiety, and negative valence) were predicted by skin conductance levels. Despite the (partial) validity of the signal, a simple algorithm that triggered the survey based on relative increases of skin conductance levels produced counterintuitive results due to a dependence between level and slope. Additional exploratory analyses highlighted other skin conductance signal characteristics (i.e. autocorrelation, number of peaks, and change points) that might be worth examining when designing future algorithms to sample arousing moments. Overall, our experiences highlight not only the promise but also the complexity of real‐time measurement of physiological processes in daily life. © 2020 The Authors. European Journal of Personality published by John Wiley & Sons Ltd on behalf of European Association of Personality Psychology